Avaliação da gestão dos resíduos gerados na construção civil no Município de Santarémpará, Brasil - SOUSA, Brenda Leticia de Mesquita (Universidade Federal do Oeste do Pará, 2024)
The objective of this study was to perform a evaluation of construction waste management in Santarém- Pará, identifying the failures and responsibilities of the actors involved in the management of Construction. The research had a qualitative-quantitative approach being performed in three phases. The research had a qualitative-quantitative approach being performed in three phases. The first phase consisted of the survey of the companies of the construction industry and contact of the same. The second phase consisted of conducting the interviews in order to gather information about the research, and finally, the third phase was to analyze the data obtained in the interviews, where it was identified that of the six construction companies studied, only four have the management plan of them to comply with the legislation. The generation of waste varies according to the size of the work and the capacity to reuse them. In general, all the builders generate several types of waste without their works, according to the results, wood is the most reused type of waste, with a reuse rate of 83%, ceramic obtained 66% and concrete 50%. As for the factors that make it difficult to manage waste within the work, the construction companies cited the storage location and the employees' awareness, as main factors, with which we can see a deficiency in the management of this waste. Based on the data found, the research reinforces the need to adopt measures to improve the management of construction waste.